On the Maieutic Function of the Methodology of History - Wrzosek, Wojciech (Sensus Historiae, 2022)
The paper is an expanded answer to voices in the discussion between Professors Jan Pomorski and Rafał Stobiecki on the so-called unintelligibility of the methodology of history. The paper argues for the philosophical provenance of the intricacies of methodological discourse. The crucial issue is the role played by questions and answers in reaching an agreement and understanding between the community of meta-historians and historians.